Problem suvereniteta u Bosni i Hercegovini / Sovereignty Issue in Bosnia and Herzegovina - Čaušević, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Contemporary Bosnia and Herzegovina is based on Dayton International Agreement, which steps out at the same time as one of the basic and fundamental postulate of state sovereignty. Based upon this, the author analyses the sovereignty problem from the aspects of philosophical reflexing, political, legal framework and state and legal development of Bosnia and Herzegovina. The problem analysis of the sovereignty has been elaborated through the analysis of independence, supremacy and legal non-determination of the authority in Bosnia and Herzegovina. Furthermore, the sovereignty problem has been explained throughout state (dis)continuity of Bosnia and Herzegovina in former Yugoslavia (federal state), which has been done through explanation of legitimacy, legality and sovereignty of Bosnia and Herzegovina (federal unit) according to Constitutions from 1946, 1963 and 1974. The character of federal constitution of Yugoslavia points out notorious fact that sovereignty undoubtedly and exclusively belongs to federation, since the one is exclusive international subject and the bearer of disposition with Kompetenz-Kompetenz (the ability of determination of its own competency). According to that, it can be concluded that the competency of competency, as the most important sovereignty element in the case of Bosnia and Herzegovina, had been exclusively charged by Federal National Republic of Yugoslavia in accordance with the Constitution from 1946 (people‟s sovereignty). And, after that the Constitutions from 1963 and 1974 had been emphasizing for the sovereign rights to be realized in socialist republics. According to this, the author bases his analysis on the legal and political foundations in order to analyses the sovereignty problem of Bosnia and Herzegovina as an autonomous, independent and sovereign country. The culmination of the research when it comes to sovereignty problem is represented by analysis of authority organization and structure according to Dayton Constitution, which emphasizes the presence of a problem for constituting of sovereign rights in Dayton Constitution of Bosnia and Herzegovina.